Train Schedule Adjustment Strategies for Train Dispatch - Huaqing Mao; Zhu Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Train schedule adjustment is the identity of key components of Train Dispatch System. Manually arranging the time table is a time-consuming and error-prone process. In this work, we mainly discuss three strategies of train schedule adjustment in train dispatch. First, we propose a new algorithm to calculate the maximum traffic capacity of freight-train in Beijing-Shanghai railway. We use a VMM (Vacancy Maximum Matching) grid to find the vacancy time table of freight-train base on the passenger train schedule, and solve the possible time sequence of freight-train by searching the bottleneck of freight-train traffic capacity. Second, we study the special circumstances in China when the spring transport or the Golden Week comes. It is necessary to put on extra passenger trains, and in order to arrange the extra passenger trains, we set up a double objective model, and the experiment shows that all the extra passenger trains arrive at the terminus within 20 hours. Finally, for the speed raising adjustment or train reschedule, we propose the SIA (Schedule inherited adjustment) algorithm to reschedule the freight-train time table. We compare the results of the SIA algorithm with that of the regular method, and find that the SIA leads to better results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2483